2020
DOI: 10.1111/obes.12359
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Dynamic Effects of Income Inequality on Crime

Abstract: What happens to crime after an increase in income inequality? The microeconomics literature that attempts to answer this question often employs identification strategies that exploit external sources of variation that provide quasi‐experiments to identify causal effects. In contrast, this paper tackles this question by using structural vector autoregressions (SVAR), a methodology typically employed in modern empirical macroeconomics to identify and estimate dynamic causal effects of exogenous shocks. Unlike th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 71 publications
2
10
0
Order By: Relevance
“…Evidence somehow is mixed. Some studies have supported a positive relationship between income inequality in society and crime (Atems 2020;Choe 2008;Enamorado et al 2016;Kim et al 2020). Other studies have failed to provide evidence of the link (Neumayer 2005) or found only a weak relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence somehow is mixed. Some studies have supported a positive relationship between income inequality in society and crime (Atems 2020;Choe 2008;Enamorado et al 2016;Kim et al 2020). Other studies have failed to provide evidence of the link (Neumayer 2005) or found only a weak relationship.…”
Section: Introductionmentioning
confidence: 99%
“…The econometric models used to analyse crime rate determinants have sometimes presented methodological problems that invalidate or bias the results obtained (Atems, 2020). Undoubtedly, the most important problem these techniques pose is the appearance of endogeneity, which requires a proper estimation of the model (Bun et al, 2020; Fajnzylber et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between poverty, income inequality, and crime rates is complex. Hence, it is a controversial issue that has been debated at length in the literature (e.g., [71][72][73][74]). The conclusions from different studies often seem contradictory as they depend on the type of crime, the spatial resolution of the analyses, and the methodological and empirical approach.…”
Section: Spatial Analyses Of the Coefficientsmentioning
confidence: 99%